EVOLUTION OF ISLAMIC SOCIAL REPORTING: VIEWED FROM ISLAMIC POSITION IN THE CONTINUUM SOCIAL RESPONSIBILITY - Bayu Tri Cahya; Farida Rohmah (Jurnal Ekonomi dan Bisnis Islam | Journal of Islamic Economics and Business, 2019)
Islamic Social Reporting (ISR) is a form of reporting on social activities based on spiritual principles and community expectations holistically related to the role of companies in society and  the environment.  This  article analyzes  the evolution  and  implementation  of  Islamic Social Reporting. This study was conducted with a literature study by reviewing the empirical evidence of previous research and the legal framework used as the foundation. This study reviews the evolution of the Islamic Social Reporting literature in an effort to evaluate its current position. From the review, it is proven that companies who implement the reporting of social activities presented in the company's annual report have been at the strategic level of  the  Islamic  responsibility  continuum.  Where  the  level  of  corporate  reporting  in  this category, indicates that the company has fulfilled the principle of social responsibility. The Strategic level itself includes altruistic responsibilities such as contributive actions to the community, providing decent wages to employees, conservation of the environment, so that long-term expectations can increase credibility and the level of trust of its stakeholders. Keywords: Islamic Social Reporting, Spiritual Perspective, Responsibilities.